Cultural Organizational Communication at the Pasanggiri Mojang Jajaka Kabupaten Bandung through Tagline Sahate Ngarante Rancage - Anartia, Niki; Meltareza, Ridma (Institute of Computer Science (IOCS), 2025)
Pasanggiri Mojang Jajaka Kabupaten Bandung is a recurring competition organized by the Paguyuban Mojang Jajaka Kabupaten Bandung. Its primary purpose is to select young individuals who can best represent the youth of Bandung Regency. This event also serves as a medium to preserve and embody the organization’s core values, represented by the tagline; Sahate Ngarante Rancage which means One heart, Solidarity, Reliable. These values serve as a guidance for members and candidate roles and responsibilities of Mojang and Jajaka within both organizational and societal context. This study employs a qualitative approach, through observation, interviews, and literature review. Data were analyzed using data triangulation method to enhance the credibility and reliability findings. Interview participants included key stakeholders involved in the Pasanggiri Mojang Jajaka Kabupaten Bandung 2023, such as judges from the Culture Office and Bandung Regency, the Chairperson of the Paguyuban Mojang Jajaka Kabupaten Bandung, committee members of Pasanggiri Mojang Jajaka Kabupaten Bandung, and participants of the Pasanggiri Mojang Jajaka Kabupaten Bandung 2023. Observation data were gathered from social media published information and official event report. Literature review data comes from past research about similar topics. This study highlights the need to ensure the cultural values are truly practiced in youth organization. The findings indicate that the tagline Sahate, Ngarante, Rancage is effective support improvements in training and assessment to strengthen Mojang and Jajaka role as regional tourism ambassador. However, observation indicates a room for improvement in terms of practical execution of the values. A deeper understanding and practical implementation among all members needed to ensure the alignment between values and practice within the organization.